Design of a smart prefabricated sanitising chamber for COVID-19 using computational fluid dynamics - Abu-Zidan, Yousef; Nguyen, Kate; Mendis, Priyan; Setunge, Sujeeva; Adeli, Hojjat (Journal of Civil Engineering and Management, 2021)
The novel coronavirus (SARS-CoV-2) has spread at an unprecedented rate, resulting in a global pandemic (COVID-19) that has strained healthcare systems and claimed many lives. Front-line healthcare workers are among the most at risk of contracting and spreading the virus due to close contact with infected patients and settings of high viral loads. To provide these workers with an extra layer of protection, the authors propose a low-cost, prefabricated, and portable sanitising chamber that sprays individuals with sanitising fluid to disinfect clothing and external surfaces on their person. The study discusses computer-aided design of the chamber to improve uniformity of sanitiser deposition and reduce discomfort due to excessive moisture. Advanced computational fluid dynamics is used to simulate the dispersion and deposition of spray particle, and the resulting wetting pattern on the treated person is used to optimise the chamber design.